Evidence of sexual transmission of Toxoplasma gondii in goats - Santana, Luis Fernando; Rossi, Gabriel Augusto Marques; Gaspar, Roberta Cordeiro; Pinto, Vanessa Marigo Rocha; Oliveira, Gilson Pereira de; Costa, Alvimar José da (Elsevier, 2013)
Male goats of reproductive age that were serologically negative for Toxoplasma gondii were selected and distributed according to the following arrangement: (A) one goat infected orally with 2.0 × 105 oocysts; (B) one goat infected subcutaneously with 1.0 × 106 tachyzoites; and (C) one uninfected goat kept as a control. After T. gondii inoculation, 12 non-pregnant female breeder goats that were serologically negative for the main reproductive diseases, especially toxoplasmosis, were synchronized and then exposed to natural mating by the males that had previously been inoculated: five females exposed to natural mating by male A (group GI); five females exposed to natural mating by male B (group GII); and two females exposed to natural mating by the uninfected male C (group GIII). In serum samples obtained from all the female goats before and after natural mating, the presence of antibodies against T. gondii was investigated using the ELISA test. PCR was performed on semen samples, on females and fetal tissues and placenta. Ten out of the 12 females showed specific antibodies against T. gondii after natural mating: five in GI and five in GII. On several dates on which natural mating occurred, T. gondii was identified in semen samples from the infected males, using PCR. Subsequently, after the females had been sacrificed, it was also possible to identify T. gondii in tissue samples from the infected females and from their fetuses, stillbirths and offspring, using PCR. Therefore, these results prove, for the first time, that T. gondii infection can be transmitted sexually from male to female goats. © 2013 Elsevier B.V. All rights reserved.
Keywords: ELISA; Goats; PCR; Sexual transmission; Toxoplasma gondii